Identification of bacterial strains capable of degrading Malaysian petroleum sludge / Noor Fazreen Dzulkapli ... [et al.] - Dzulkapli, Noor Fazreen; Abdul Talib, Suhaimi; Ramasamy, Kalavathy; Yin, Chun Yang (Institute of Research, Development and Commercialisation (IRDC), 2007)
In an organic sludge bio degradation process, identification of bacterial strains with effective biodegradation capabilities indigenous to the sludge is an important step as isolation and subsequent usage of such strains can enhance the rate of the biodegradation process. In this study, the identification of bacterial strains capable of degrading Malaysian petroleum sludge was carried out using a biolog system kit subsequent to enrichment, isolation and degradation processes. A total of 53 purified strains was obtained from the isolation process. Three strains, namely, Clavibacter michiganesis ss insidiosus, Rhodococcus rhodochrus and Brevibacterium otitidis showed favorable degradation results for nearly all hydrocarbons especially for polycyclic aromatic hydrocarbon (PAHs) (anthracene, phenathrane and dibenzothiophene). Brevibacterium otitidis is especially interesting since it is the first time such a strain has been reported to have good PAHs degradation capabilities.